2009
DOI: 10.1177/107327480901600111
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Demands of Written Health Information Materials: An Assessment of Cervical Cancer Prevention Materials

Abstract: (DH, CH, NO); and the Behavior Change Research Group, Population Sciences and Cancer Control Program (DH, JC) at the University of New Mexico, Albuquerque, New Mexico. Submitted August 14, 2007; accepted February 26, 2008. Address correspondence to Deborah Helitzer, ScD, Family and Community Medicine, University of New Mexico, MSC 09-5040, Albuquerque, NM 87131. E-mail: helitzer@salud.unm pitalization have been documented. [1][2][3] Evidence demonstrates that patients with lower health literacy incur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 17 publications
2
96
0
7
Order By: Relevance
“…In 2004 Wallace et al 13 found that only 7% of the American Academy of Family Practice's PEMS were written below an 8 th grade reading level. Various subspecialties such as cardiology 14,15 , infectious disease, 16 plastic surgery, 17 dermatology, 18 orthopedics, 19,20 palliative care, 21 oncology 22,23 and obstetrics and gynecology 24,25 have studied the readability of the PEMs utilized in their fields, and findings consistently indicate that 9 th -12 th grade reading levels are necessary to read and comprehend these documents.…”
Section: Patient Education Materialsmentioning
confidence: 99%
“…In 2004 Wallace et al 13 found that only 7% of the American Academy of Family Practice's PEMS were written below an 8 th grade reading level. Various subspecialties such as cardiology 14,15 , infectious disease, 16 plastic surgery, 17 dermatology, 18 orthopedics, 19,20 palliative care, 21 oncology 22,23 and obstetrics and gynecology 24,25 have studied the readability of the PEMs utilized in their fields, and findings consistently indicate that 9 th -12 th grade reading levels are necessary to read and comprehend these documents.…”
Section: Patient Education Materialsmentioning
confidence: 99%
“…Estas actividades podrían redirigir la atención de los gobiernos regionales a los establecimientos de salud del primer nivel, que sufren de múltiples carencias materiales, déficit de profesionales de salud, falta de gestión eficiente, y son justamente los que han sido más olvidados, tomando en cuenta que la falta de conocimientos sobre salud es la principal brecha entre el entendimiento entre los prestadores de salud y la población (6) .…”
Section: Retos Para La Difusión De Información Sobre Derechos En Saludunclassified
“…169 Completion of this questionnaire involves assigning a series of scores to the following aspects of the leaflet: literacy demand; numeracy; graphic material; layout and typography; and learning, stimulation and motivation. Scores are given as a percentage and a minimum The leaflet was a national and not a local intervention and so the language used had to be modified to suit a varied UK audience.…”
Section: Suitability and Comprehensibility Assessment Of Materialsmentioning
confidence: 99%
“…Finally, we evaluated the leaflet using the Suitability and Comprehensibility Assessment of Materials questionnaire. 169 These stages of development are described in more detail below.…”
Section: Introductionmentioning
confidence: 99%